What is not real can be felt into being: affective threat in Jordan Peele's Get Out. Issue 4 (2nd October 2021) - Train, Emma
ABSTRACT: Jordan Peele's (2017) Get Out presents a political critique of American post-racial discourse. Using Brian Massumi's concept of affective fact, I articulate how the film navigates a post-race perception of racially motivated threat as solely affective and immaterial in relation to the actual enactment of violence onto the racialized body in contemporary America. I locate this film in the theoretical lineage of contemporary Black radical thought, with particular emphasis on Saidiya Hartman's concept of fungibility and Stefano Harney's and Fred Moten's concept of fugitivity. By analyzing scenes that inaugurate the film's study of threat, surveillance, and state-mandated control, I argue that Get Out reveals how apparatuses of racial violence intertwine with what Harney and Moten call state-thought. I conclude that Get Out should be read as a commentary on Black cinema and Black aesthetics, particularly how Black aesthetics forms itself against, within, and around neoliberal political discourse.